Acute urinary retention in a 14-year-old girl – diagnostic and therapeutic difficulties when initial therapy fails - Łyszkowicz, Michał Janusz; Stańczyk, Małgorzata Barbara; Krakós, Marek; Przysło, Łukasz; Tkaczyk, Marcin (Pediatria Polska - Polish Journal of Paediatrics, 2024)
Acute urinary retention is rare in children and has various causes, but in 10% of cases has unclear aetiology. It is more common in boys and is often associated with urinary tract inflammation or mechanical obstruction. A 14-year-old girl presented with urinary retention preceded by haematuria and abdominal pain. Catheterisation drained 900 ml of urine, and symptoms initially subsided after taking α-blockers and oxybutynin. However, urinary retention reoccurred and persisted. Cystometry demonstrated bladder insensitivity, decreased detrusor activity, and increased sphincter tone. Suprapubic urinary diversion was performed. Neurological and magnetic resonance imaging examinations were normal, but cerebrospinal fluid showed IgG antibodies that reacted with sulfatide antigens. Immunosuppressive treatment was ineffective. Eventually administration of distigmine and baclofen permanently restored bladder function within a week. Persistent urinary retention is very distressing. Prompt diagnosis is possible, but managing idiopathic cases poses challenges, requiring a multidisciplinary approach. Evaluation based on knowledge of organ innervation is crucial.